ANALYSIS OF TEENAGER’S SHORT MESSAGE SERVICE STYLE - Jimmi Jimmi; Juniato Sidauruk (Wanastra: Jurnal Bahasa dan Sastra, 2014)
Nowadays, the invention of technology especially mobile phone leads society beyond transformation of technology and its devices. The transformation can be seen clearly in whole communication aspects. By using mobile phone, people are able to communicate and utilize their language limitless.The features which is found in mobile phone such as voice call, video call, Media Message Service (MMS), and Short Message Service (SMS). These features can make people are able to communicate anytime and anywhere. A SMS service, one of mobile phone’s features, is limited by the number of characters. By this reason, this paper is going to bring a clear description about several styles ofSMS. This limits forces many people to be creative in arranging their ideas in the form of sentences in SMS. They, then clip the sentences, mix letters with numbers, put symbols and so forth in order to overcome character’s limit problem. This kind of creativity leads them to invent a new languagestyle known as SMS language. Unfortunately, since there is no convention about how to write SMS, every people tends to invent their own style in writing SMS. As a result, various styles of writing SMS are found. This phenomenon becomes interesting to be learnt based on linguistic approached.